DAMPAK LAGU SATU NUSA SATU BANGSA PADA MOTIVASI BELAJAR SISWA KELAS V SD NEGERI 29 NENAK TEMBULAN SINTANG KALIMANTAN BARAT - Rusdi, Rusdi; Warkintin, Warkintin; Wibowo, Dwi Cahyadi; Sari, Dian Wahidah (STKIP Persada Khatulistiwa Sintang, 2025)
The purpose of this study was to examine the impact of the song Satu Nusa Satu Bangsa on the learning motivation of fifth-grade students at SD Negeri 29 Nenak Tembulan, Sintang, West Kalimantan. The study employed a qualitative research design using a taxonomic analysis approach. The research subjects included teachers, school administrators, students of SD Negeri 29 Nenak Tembulan, and experts in education and music learning. Data collection was carried out through perception-based observations and music listening activities. Data were analyzed through field observations and by examining the students' conditions in the classroom while listening to the song Satu Nusa Satu Bangsa. The results indicated that, based on observations, students showed seriousness and spontaneously sang Satu Nusa Satu Bangsa. After listening to the song, students' learning motivation increased, as evidenced by their enthusiasm in singing and internalizing the message of the song. Following the singing activity, students appeared more refreshed, more enthusiastic about receiving lessons, and more prepared for learning activities. This study offers insights for classroom teachers, suggesting that listening to or singing a national song before beginning a lesson can positively impact students' learning motivation.